Potential of Areca catechu Nut Extract for Osteoarthritis: Study on Rat Model - Humaryanto Humaryanto; Ave Olivia Rahman; Fairuz Quzwain (Wolters Kluwer - Medknow Publications, 2023)
Introduction: Osteoarthritis (OA) is a leading cause of disability among aged people. Commonly used, nonsteroidal anti-inflammatory drugs do not give significant results without side effects. Areca catechu seed has an anti-inflammatory effect. The objective of this research is to evaluate the anti-inflammatory effect of A. catechu extract on rat model of OA. Methods: Research design was posttest only with control groups. Male Sprague Dawley rats weighed 175-200 g and were induced by monosodium iodoacetate to make OA modeling. Rats were randomly divided into four groups, namely Group 1 received 120 mg/200 g BW A. catechu extract, Group 2 received 360 mg/200 g BW A. catechu extract, Group 3 received 0.270 mg/200 g BW meloxicam, and Group 4 received distilled water as a negative control. Treatments were given started 7 days' postinduction for 28 days. Rats' knee was measured using micrometer digital. Histopathology assessment using Haematoxylin and Eosin stain. Statistical analysis used one way ANOVA test with a significance level P < 0.05. Results: After 28 days of treatment, the means of diameter differences after treatment and before treatment were 0.186 ± 0.23 in Group 1; 0.526 ± 0.26 in Group 2; 0.206 ± 0.12 in Group 3; and 0.626 ± 0.33 mm (mm) in Group 4. A dose of 120 mg/200 g BW of A. catechu reduces joint inflammation to the same extent as meloxicam (P > 0.05). The histopathology of knee join among the treatment's groups was improved with time. Conclusion: A. catechu has an effect on reducing joint inflammation of the knee after OA induction by monosodium iodoacetate.